Comparison of Two Dosing Regimens of Miltefosine, Both in Combination With Allopurinol, on Clinical and Parasitological Findings of Dogs With Leishmaniosis: A Pilot Study - Iarussi, Fabrizio; Paradies, Paola; Foglia Manzillo, Valentina; Gizzarelli, Manuela; Caratozzolo, Mariano Francesco; Navarro, Christelle; Greco, Beatrice; Rubino, Giuseppe Tommaso Roberto; Oliva, Gaetano; Sasanelli, Mariateresa (Frontiers in Veterinary Science, 2020)
Miltefosine (MIL)–allopurinol combination therapy administered at standard dosage is effective to treat canine leishmaniosis, nevertheless for some dogs the digestive tolerance of MIL is not acceptable. This study evaluates an alternative therapeutic protocol by using a modified dosage of MIL to increase its effectiveness and improve the digestive tolerance. Thirty-four Leishmania infantum owned naturally infected dogs were included and monitored for 180 days. The dogs were allocated in two randomized groups: Group X−18 dogs treated with MIL registered dose of 2 mg/kg, oral administration, once daily, for 28 days; Group Y−16 dogs treated with 1.2 mg/kg for 5 days followed by 2.5 mg/kg for 25 days. Both groups were also treated with allopurinol. Digestive tolerance was monitored by adverse events observation. Treatments effectiveness was evaluated by monitoring the reduction of clinical score, the improvement of clinicopathological abnormalities, the reduction of parasitological load by PCR and the number of relapses. 16.6% dogs of group X and 12.5% dogs of group Y showed treatment associated adverse events. The reduction of clinical score was 61.7% for group X and 71.6% for group Y. All dogs showed an improvement of laboratory parameters after treatment. Quantitative PCR showed better results in group Y compared to group X; relapses were only registered in four dogs of group X. The modified protocol demonstrates a better trend of results in term of tolerance, clinical effectiveness, parasitological load reduction and relapses control, suggesting it could be considered for new large-scale studies.